Isolation, screening and identification of microorganisms having antimicrobial activity and causing cytotoxicity isolated from sediment samples of the Vung Ang bay in Ha Tinh - Quyen, Vu Thi; Thu Huyen, Vu Thi; Mai Anh, Nguyen; Hai Dang, Nguyen; Mai Huong, Doan Thi; Van Cuong, Pham; Hong Minh, Le Thi (Vietnam Journal of Biotechnology, 2021)
Actinomycetes has been extensively studied due to its ability to produce secondary compounds with high application value. Especially their antibiotic ability, more than 40% of antibiotics are derived from actinomycetes of which genus Streptomyces predominates. Moreover, marine actinomycetes have been being of great interest in recent years due to their ability to produce bioactive substances capable of providing diverse and novel chemical structures. In this study, from 8 samples of marine sediments collected in Vung Ang bay in Ha Tinh provinces, we have isolated 20 strains of actinomycetes. The strains were fermented in A1+ medium, the fermentation fluid was extracted 5 times with ethyl acetate, recovered sediment and determined antibacterial and cytotoxic activity. From the screening results, two strains with the highest antibacterial activity and highest cytotoxicity were selected ie., HT03 and HT06. Both strains had antagonistic activity of Enterococcus faecalis ATCC29212 with MICHT03= 32 μg/mL, MICHT06= 16μg/mL, with Stapphylococus aureus ATCC25923 with MICHT03= 64 μg/mL, MICHT06= 32 μg/mL and with Bacillus cereus ATCC 13245 has the same MIC = 16 μg / mL. In addition, the two strains HT03 and HT06 were able to strongly inhibit the yeast Candida albicans ATCC10231 with MICHT03= 16 μg/mL, MICHT06= 8 μg/mL. Especially, two strains, HT03 and HT06, exhibited very good toxicity on all 5 cancer cell lines (MCF-7 breast cancer cell; MDA-MB-231 breast cancer cell; lung cancer cell). NCI-H1975; HeLa cervical cancer cell; AGS gastric cancer cell) at both test concentrations of 30 µg/mL and 100µg/mL. By the analysis of 16S rRNA sequence, the results showed that the HT03 strain had the highest similarity (99.93%) to that of Streptomyces fradiaes and Streptomyces fradiae ATCC. The HT06 strain was defined to belong to Nocardiopsis synnemataformans with the 16S sequence identity of 99.89% to the Japanese standard Nocardiopsis synnemataformans DSM 44143 strain NBRC-102581.